2020
DOI: 10.7326/m19-0735
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, Safety, and Efficacy of a Standalone Universal Influenza Vaccine, FLU-v, in Healthy Adults

Abstract: InterventionsFLU-v is a sterile 500-μg equimolar mix of 4 lyophilized synthetic peptides (5) (Appendix Table 1, available at Annals.org). Montanide ISA-51 (mineral oil/ mannide monooleate) (SEPPIC) was used as an adjuvant to enhance immune responses to FLU-v antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…It has been proposed that vaccination with conserved epitopes of influenza virus can result in broad protection. Universal vaccination has now been developed and is undergoing clinical trials [ 56 , 57 ]. Therefore, our strategy is valuable before the availability of an effective and safe universal influenza vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that vaccination with conserved epitopes of influenza virus can result in broad protection. Universal vaccination has now been developed and is undergoing clinical trials [ 56 , 57 ]. Therefore, our strategy is valuable before the availability of an effective and safe universal influenza vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Flu-v consists of conserved peptides derived from M1, M2, and NP formulated with Montanide ISA-51 as an adjuvant. The vaccine induces cellular immunity in humans, and could reduce symptoms and viral shedding in a small human challenge study [150,151]. A recently published phase IIb study showed only a limited capacity of the vaccine to protect against mild to moderate influenza disease in experimental infections.…”
Section: Clinical Studies Of T Cell-inducing Flu Vaccinesmentioning
confidence: 99%
“…In turn, FLU-v, developed by PepTcell (SEEK), is a peptide vaccine comprised of four synthetic peptides with conserved epitopes from influenza A and B strains designed to provide a broadly protective cellular immune response against influenza A and B. Results from phase IIb clinical trials showed that adjuvanted FLU-v recipients ( n = 40) were significantly less likely to develop mild to moderate influenza disease (MMID) following intranasal challenge of A/CA04/H1N1 vs. placebo ( n = 42) (32.5 vs. 54.8% p = 0.035) [ 69 , 70 , 71 ]. Nevertheless, overall the vaccine protection effect was poor.…”
Section: Novel Universal Influenza Vaccinesmentioning
confidence: 99%